Evaluating the Impact of Maritime Regulations: Balikpapan Port's Readiness in Supporting the Nusantara Capital Project - Hidayat, Luqman Sariful; Ekowanti, Mas Roro Lilik; Casmiwati , Dewi (Journal of Social and Policy Issues, 2024)
This study aims to evaluate the impact of Government Regulation Number 31 of 2021 concerning the Administration of the Shipping Sector in supporting the Nusantara Capital City, using Balikpapan Port as a case study. The research employs a descriptive method with a qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed using the Miles, Huberman, and Saldana model, encompassing four stages: data collection, data condensation, data analysis, and conclusion drawing. The findings reveal that while the program has not been fully implemented, improvements in port administration, capabilities, roles, and maritime environmental protection have been achieved. Over the past five years (2018–2022), vessel visits increased by an average of 24.3% annually (units) and 21.8% (gross tonnage). Foreign cargo services rose by 12.15% annually for exports and 16.41% for imports, contributing to an average economic growth of 1.71% per year in Balikpapan City (2019–2023). Additionally, maritime environmental protection has led to the development of new tourist destinations. However, challenges such as ship thefts and limited fishing grounds for local fishermen persist. In the future, the Nusantara Capital City may face waterway congestion, potentially disrupting traffic and increasing the risk of maritime accidents.